Immunopathogenesis of childhood idiopathic nephrotic syndrome - Hae Il Cheong (Korean Society of Pediatric Nephrology, 2023)
Pediatric nephrotic syndrome (NS) is a clinical syndrome characterized by massive proteinuria, hypoalbuminemia, and generalized edema. Most childhood NS cases are idiopathic (with an unknown etiology). Traditional therapeutic approaches based on immunosuppressive agents largely support the key role of the immune system in idiopathic NS (INS), especially in the steroid-sensitive form. Although most previous studies have suggested the main role of T cell dysfunction and/or the abnormal secretion of certain glomerular permeability factors, recent studies have emphasized the role of B cells since the therapeutic efficacy of B cell depletion therapy in inducing and/or maintaining prolonged remission in patients with INS was confirmed. Furthermore, several studies have detected circulating autoantibodies that target podocyte proteins in a subset of patients with INS, suggesting an autoimmune-mediated etiology of INS. Accordingly, a new therapeutic modality using B cell-depleting drugs has been attempted, with significant effects in a subset of patients with INS. Currently, INS is considered an immune-mediated disorder caused by a complex interplay between T cells, B cells, soluble factors, and podocytes, which may vary among patients. More in-depth investigations of the pathogenic pathways of INS are required for an effective personalized therapeutic approach and to define precise targets for therapeutic intervention.